2015
DOI: 10.1155/2015/703029
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Mechanical Properties of Composites Made with Aluminous Cement and Basalt Fibers Developed for High Temperature Application

Abstract: Present paper deals with the experimental study of the composition of refractory fiber-reinforced aluminous cement based composites and its response to gradual thermal loading. Basalt fibers were applied in doses of 0.25, 0.5, 1.0, 2.0, and 4.0% in volume. Simultaneously, binder system based on the aluminous cement was modified by fine ground ceramic powder originated from the accurate ceramic blocks production. Ceramic powder was dosed as partial replacement of used cement of 5, 10, 15, 20, and 25%. Influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…It must be noted that FGCP had already gone through exposure to elevated temperature during brick production, which could be successfully exploited in the composition formulation of refractory castables. is approach was con rmed in previous research [16,34]. In addition, Table 1 shows the chemical composition of the studied FGCP, when the total amount of Al 2 O 3 is 13.98% and SiO 2 is 64.45%.…”
Section: Fine Ceramic Powdersupporting
confidence: 70%
See 1 more Smart Citation
“…It must be noted that FGCP had already gone through exposure to elevated temperature during brick production, which could be successfully exploited in the composition formulation of refractory castables. is approach was con rmed in previous research [16,34]. In addition, Table 1 shows the chemical composition of the studied FGCP, when the total amount of Al 2 O 3 is 13.98% and SiO 2 is 64.45%.…”
Section: Fine Ceramic Powdersupporting
confidence: 70%
“…Also the drying process could cause cracks; therefore, the fibers limit the crack propagation [15]. e previous research confirmed that optimal dosage of basalt fibers, in terms of residual mechanical and fracture properties, in fine-grained cement-based composite lies between 1.0 and 2.0% by volume [16] or 4% of ceramic fibers, respectively [17].…”
Section: Introductionmentioning
confidence: 99%
“…In Table 2, the bulk density, flexural strength, compressive strength and fracture energy of used mixtures are shown (after exposure to 105°C, 600°C and 1000°C). All mentioned properties were measured on specimens with dimensions of 40 × 40 × 160 mm and are taken from [24].…”
Section: Composition Of Used Mixturesmentioning
confidence: 99%
“…In previous research [11,23,24], the influence of elevated temperatures on various properties of refractory composites has been investigated after exposure to one loading cycle. In accordance with the goal of this research, the temperature loading scheme was modified.…”
Section: Cycling Temperature Loadingmentioning
confidence: 99%
“…For the purpose of the ultra-high performance fibre reinforced concrete (UHPFRC), the high strength steel fibres are commonly used, where the optimal dosage oscillates from 1.5 % to 2.0 % of volume [12,13]. The optimal dosage of fibres in the field of refractory composite has also been investigated, where the amount from 1.0 % to 2.0 % of basalt fibres can be classified as suitable for an elevated environment [14]. The optimal dosage of ceramic fibres can be found in a level about 4.0 % [15].…”
Section: No /mentioning
confidence: 99%